DEMOKRASI DAN POLITIK MINORITAS DI INDONESIA - Muhammad Imaduddin Nasution (Sekretariat Jenderal DPR RI, 2013)
In Indonesia, the minority groups have a fairly high political awareness. However the minority in Indonesia have also realize a very democratic Indonesia, with higher political participation of citizens, above the participation of United States citizens. However, the actual political participation of minorities in Indonesia is facing a big problem. Discrimination, religious issues and ethnical issues ever coloring the ritual of democracy in Indonesia. In the meantime, the obligation to choose one of six “official” religions, being a form of discrimination against the other religions. This article will discuss the concepts of participation and political representation of minorities, the matters of integration of minority groups and the rights of identity of the minorities in the context of minority politics and identity politics. This article will also discuss the Christian minority politics in Indonesia, which is followed by discussion of the politics of identity of the other minority groups in Indonesia. This article was written to show how the minority politics, political participation rights and obligations, as well as their influence in Indonesian politics are exerevised.